2011
DOI: 10.1038/cddis.2011.64
|View full text |Cite|
|
Sign up to set email alerts
|

Celecoxib and acetylbritannilactone interact synergistically to suppress breast cancer cell growth via COX-2-dependent and -independent mechanisms

Abstract: The use of celecoxib is associated with a significant decrease in breast cancer risk. However, the long-term use of high-dose celecoxib might be limited owing to cardiovascular side effects. In this study, we found that acetylbritannilactone (ABL), extract from a Chinese medicinal herb, could reduce celecoxib dose and potentiate the growth-inhibitory effect in breast cancer cells. ABL enhanced the apoptotic effect of celecoxib in COX-2-expressing cells, but had little effect in COX-2-negative cells. The apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 42 publications
(54 reference statements)
1
16
0
Order By: Relevance
“…Abundant studies indicate that celecoxib suppress cell proliferation and carcinogenesis through different mechanism [22,23]. Celecoxib is shown to suppress breast cancer cells growth through COX-dependent mechanism and the inhibitory effects are disappeared when COX-2 is knocked down [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abundant studies indicate that celecoxib suppress cell proliferation and carcinogenesis through different mechanism [22,23]. Celecoxib is shown to suppress breast cancer cells growth through COX-dependent mechanism and the inhibitory effects are disappeared when COX-2 is knocked down [22].…”
Section: Discussionmentioning
confidence: 99%
“…Celecoxib is shown to suppress breast cancer cells growth through COX-dependent mechanism and the inhibitory effects are disappeared when COX-2 is knocked down [22]. The evidence from in vitro and in vivo experiments indicates that the underlying mechanism responsible for the anticancer activities of celecoxib involves the induction of cell apoptosis [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Cells were plated in 24-well plates, then the cells were co-transfected with NF-κB-Luc plasmid and the internal control plasmid renilla luciferase (pRL-TK) using transfection reagent Lipofectamine 2000 (Invitrogen, Carlsbad, CA) as described previously [25]. The cells were harvested after aspirin treatment, and the luciferase activity was measured using the Dual Luciferase Reporter Assay System (Promega, Madison, WI).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were treated and then the cells were prepared with lysis buffer and western blot analysis was performed [25]. The proteins were separated by 10% SDS-PAGE, then transferred onto PVDF membranes and blotted with primary antibodies against Histone H2B (1: 400), β-actin (1: 400), NF-κB p65 (1: 400), IκB-α (1: 1000), phospho-IκB-α (1: 1000), IKK-α (1: 1000), IKK-β (1: 1000) and phospho-IKK-α/β (1: 1000) at 4°C overnight, and then incubated with the secondary antibody (1: 10000) for 2 h. The blots were normalized against β-actin or Histone H2B.…”
Section: Methodsmentioning
confidence: 99%
“…Despite epidemiological and experimental evidence indicating an important role for the use of celecoxib, a highly selective COX-2 inhibitor, in the treatment and prevention of NSCLC (4,5), the exact mechanism remains unclear. Conversely, however, recent studies have shown that even the highly selective COX-2 inhibitors have potential side effects (6). These agents should, therefore, be used at a low dosage.…”
Section: Introductionmentioning
confidence: 99%